Analisis Strategi Pemasaran Produk Untuk Meningkatkan Kinerja Pada Toko Kue Island Cake Metro - Ratmono; Durotun Nasikah; Ajeng Resmadi Putri (Universitas Muhammadiyah Metro, 2024)
The purpose of this study was find out how the marketing performance, the internal and theexternal factors of the Island Metro Cake Shop, and what kind of marketing strategy isappropriate to improve its marketing performance. This study applied a qualitative researchmethod by analyzing the product marketing strategy at the Metro town Cake Shop IslandCake. The collection of this research data involved two informants, they were cake shopowners and his employee. The research data were obtained by conducting interviews anddistributing questionnaires to determine the weights and ratings on aspects of the company'sinternal and external factors. Data analysis in this study used a SWOT analysis consisting ofStrengths, Weaknesses, Opportunities and Threats. The results of this study indicated that themarketing performance of the island cake cake shop in Metro town seemed to have a fairlygood performance. This is based on the sales results achieved by the island cake shop whichhas increased from year to year. The number of costumers who buy the products in the formof cakes at island cake shops is increasing. The marketing strategy implemented by the shopowner is to provide good service quality, ease of service, and promote on social media. Basedon the SWOT analysis, the strategy in marketing Island Cake shop products applies EFE andIFE analysis as a grow and build strategy within the company. The shop maintains service to customers by maintaining the superiority of its cake products both in terms of quality andquantity.